An emission spectrum for WASP-121b measured across the 0.8–1.1 μm wavelength range using the Hubble Space Telescope. Issue 2 (27th June 2019) - Mikal-Evans, Thomas; Sing, David K; Goyal, Jayesh M; Drummond, Benjamin; Carter, Aarynn L; Henry, Gregory W; Wakeford, Hannah R; Lewis, Nikole K; Marley, Mark S; Tremblin, Pascal; Nikolov, Nikolay; Kataria, Tiffany; et al.
Abstract: WASP-121b is a transiting gas giant exoplanet orbiting close to its Roche limit, with an inflated radius nearly double that of Jupiter and a dayside temperature comparable to a late M dwarf photosphere. Secondary eclipse observations covering the 1.1–1.6 μm wavelength range have revealed an atmospheric thermal inversion on the dayside hemisphere, likely caused by high-altitude absorption at optical wavelengths. Here we present secondary eclipse observations made with the Hubble Space Telescope Wide Field Camera 3 spectrograph that extend the wavelength coverage from 1.1 μm down to 0.8 μm . To determine the atmospheric properties from the measured eclipse spectrum, we performed a retrieval analysis assuming chemical equilibrium, with the effects of thermal dissociation and ionization included. Our best-fitting model provides a good fit to the data with reduced χ ^2_ν =1.04 . The data diverge from a blackbody spectrum and instead exhibit emission due to H − shortward of 1.1 μm . The best-fitting model does not reproduce a previously reported bump in the spectrum at 1.25 μm, possibly indicating this feature is a statistical fluctuation in the data rather than a VO emission band as had been tentatively suggested. We estimate an atmospheric metallicity of [M/H]= 1.09_-0.69^+0.57, and fit for the carbon and oxygen abundances separately, obtaining [C/H]= -0.29_-0.48^+0.61 and [O/H]= 0.18_-0.60^+0.64 . The corresponding carbon-to-oxygen ratio is C/O = 0.49_-0.37^+0.65, which encompasses the solar value of 0.54, but has a large uncertainty.